PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn KELAS V SD NEGERI 011 BUKIT GAJAH KECAMATAN UKUI - Jasman R (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research stems from low Civics (PKn) learning outcomes, characterized by an average student score of 67.2, which is below the established Minimum Completeness Criteria (KKM) of 75. Furthermore, only 9 students, or 37.80%, achieved complete study results. Based on this, the researchers aimed to improve learning through action research by applying the Student Teams Achievement Divisions (STAD) cooperative learning model. This study was conducted over two cycles, each consisting of two meetings and one daily test. The subjects were fifth-grade students of SD Negeri 011 Bukit Gajah. Data collection techniques included observation of teacher and student activities, as well as Civics test results. The study indicates that the implementation of the STAD cooperative learning model can improve student learning outcomes in Civics. This is evidenced by: (a) the activities of teachers increasing in each cycle. In the first cycle, the teacher's activity in the first meeting received a score of 15, or 62.5%, categorized as "good." In the second meeting of the first cycle, teacher activity obtained a score of 19, or 79.2%, also categorized as "good." In the first meeting of the second cycle, the teacher's activity obtained a score of 22, or 91.7%, with a "very good" category. In the second meeting of the second cycle, teacher activities were given a score of 23, or 95.8%, with a "very good" category. Student activities also increased in each cycle. In the first cycle, the first meeting of student activity obtained a score of 13, or 54.2%, categorized as "sufficient." In the second meeting of the first cycle, student activities obtained a score of 17, or 70.8%, categorized as "good." In the first meeting of the second cycle, student activity obtained a score of 20, or 83.3%, with a "very good" category. In the second meeting of the second cycle, student activities obtained a score of 21, or 87.5%, with a "very good" category; and (b) student learning outcomes increased. This is demonstrated by the average student learning outcomes increasing by 13.1% from a baseline score of 67.2 to 77.3 in Cycle I. In the second cycle, the average increased by 24.7% from a baseline score of 67 to 83.8. Classical completeness increased from a baseline score of 37.8% to 71.1% in the first cycle and 93.3% in the second cycle.